Monitorização das etapas envolvidas na terapia de nutrição parenteral neonatal em uma maternidade pública de Fortaleza - Mascarenhas, Mylenne Borges Jácome (2009)
Many newborns (NB) require total parenteral nutrition (TPN) as main or adjuvant therapy, once they can not obtain an adequate nutrition through gastrointestinal system. The TPN offers to the debilitated patient the necessary electrolytes, the required protein source and the energy for metabolic processes. The nutritional therapy phases are: indication for nutritional support; medical prescription; pharmaceutical evaluation; manipulation of the solutions; delivery; conservation; administration; clinical and laboratorial controlling; and, final evaluation. Due to the complexity of the steps involved, it is important the integration of the multidisciplinary team, so that the therapy is used rationally, resulting in benefits to the NB in terms of safety, effectiveness and quality. The present work aimed to monitor the nutritional therapy in NB, observing the indication, prescription, manipulation and administration of the parenteral nutrition in a public maternity in Fortaleza – CE. It was performed an observational, descriptive and prospective study involving all phases. The data were collected from a structured formulary according to the inspection rule (Portaria 272/98, ANVISA). The statistical analysis was executed using the program Statistical Package for the Social Sciences, version 16.0, and it was considered a significance level of 5%. Among the 73 NB evaluated, 97,3% presented as main diagnostic pre-term newborn. Related to the medical prescriptions, 2,3% were not delivered to the pharmacy, 16,7 and 9% were delivered out of the established time and with problems in the prescriptions, respectively. During the manipulation, 0,6 and 6,15% of errors occurred, respectively in the aspiration or in the addition of the substances. At the moment of the administration, 99% of the NB did not have exclusive access for the TPN; neither 98,7% of the bags nor 99% of the labels were adequately checked. In 36% of catheter placement, no cleaning procedure was performed. In conclusion, the controlling of process involved in nutritional therapy and a more active multidisciplinary team will assess the correction of deviations and errors, once the prescription, manipulation and administration represent the critic steps for a successful therapy.